Bhagavad Gita and Modern Psychiatry: A Framework for Psycho spiritual Healing (Journal of Nobel Medical College, 2025)
Background: This paper explores how the therapeutic principles of the Bhagavad Gita can be integrated with modern psychiatry to heal patients through psycho-spiritual approaches.Methods: This is a comparative historical study design of qualitative nature. It analyzes the teachings such as dharma (righteous action), vairāgya (detachment), abhyāsa (practice), and ātma-jñāna (self-knowledge) and links them to clinical goals like emotional regulation, identity formation, and cognitive clarity. It compares ancient guidance to modern psychological constructs. The study uses Eknath Easwaran’s translation to highlight verses that align with therapeutic principles. It focuses on the emotional journey of Arjuna, one of the key characters and the disciple of Krishna. It highlights Krishna and Arjuna doctor-patient relationship respectively.  It describes Arjuna’s breakdown and his path to recovery. The study also explores how Krishna like a doctor employs therapeutic techniques to address Arjuna’s symptoms of anxiety, confusion, and identity loss. Krishna’s techniques reflect the strategies tantamount to cognitive behavioral therapy, mindfulness, and existential approaches. The paper observes emotional transformation of Arjuna which parallels with therapeutic approaches like self-reflection, value alignment, and mental resilience. It also reviews recent medical literatures which support integrating Gita-based ideas in mental health care. It cites articles that compare Gita dialogue to cognitive behavioral therapy (CBT), interpersonal therapy, and mindfulness. It also shows how one can reduce stress, increase life satisfaction, and cope with anxiety. It also explores how Gita techniques such as controlled breathing and meditation can be harmonized with mindfulness training.Conclusion: The paper argues that the Gita, as a psychological guide, offers a structured path to inner balance and self-understanding. It contends that lessons on detachment and duty help regulate emotions and clarify values. Gita’s psychological approach bolsters ethical, spiritual, and cultural insight of modern psychiatry. It bridges Western clinical models with indigenous wisdom. The paper further unveils how Gita’s psychological tools complement evidence-based methods and reinforce therapeutic outcomes and collaborate between psychiatry, psychology, and spiritual studies, offering clarity, purpose, and peace to those in distress. It positions the text as a universal resource that enriches holistic therapy.